A phase II trial evaluating the efficacy and safety of perioperative pirfenidone for prevention of acute exacerbation of idiopathic pulmonary fibrosis in lung cancer patients undergoing pulmonary resection: West Japan Oncology Group 6711 L (PEOPLE Study). Issue 1 (December 2016) - Iwata, Takekazu; Yoshino, Ichiro; Yoshida, Shigetoshi; Ikeda, Norihiko; Tsuboi, Masahiro; Asato, Yuji; Katakami, Nobuyuki; Sakamoto, Kazuhiro; Yamashita, Yoshinori; Okami, Jiro; Mitsudomi, Tetsuya; Yamashita, Motohiro; et al.
Abstract Background Idiopathic pulmonary fibrosis (IPF) often accompanies lung cancer, and life-threatening acute exacerbation (AE) of IPF (AE-IPF) is reported to occur in 20 % of IPF patients who undergo lung cancer surgery. Pirfenidone is an anti-fibrotic agent known to reduce disease progression in IPF patients. A phase II study was conducted to evaluate whether perioperative pirfenidone treatment could reduce the incidence of postoperative AE-IPF patients with lung cancer. Methods Pirfenidone was orally administered to IPF patients who were candidates for lung cancer surgery; pirfenidone was dosed at 600 mg/day for the first 2 weeks, followed by 1200 mg/day. Surgery was performed after at least 2 weeks of 1200-mg/day administration. The primary endpoint was non–AE-IPF rate during postoperative days 0–30, compared to the null value of 80 %, and the secondary endpoint was safety. Radiologic and pathologic diagnoses of IPF and AE-IPF were confirmed by an independent review committee. Results From June 2012 to January 2014, 43 cases were enrolled, and 39 were eligible (full analysis set [FAS]). Both pirfenidone treatment and surgery were performed in 36 patients (per protocol set [PPS]). AE-IPF did not occur in 37/39 patients (94.9 % [95 % confidential interval: 82.7–99.4 %, p = 0.01]) in the FAS, and in 38/39 patients (97.2 % [95 % confidential interval: 85.5–99.9 %, p = 0.004] in the PPS. A grade 5 adverse event (death) occurred in 1 patient, after AE-IPF; no other grade 3–5 adverse events were observed. Conclusions Perioperative pirfenidone treatment is safe, and is promising for reducing AE-IPF after lung cancer surgery in IPF patients. Trial registration This clinical trial was registered with the University Hospital Medical Information Network (UMIN) on April 16th, 2012 (Registration Number:UMIN000007774 ).